Pemberdayaan Masyarakat Desa Jlarem Kecamatan Gladagsari Kabupaten Boyolali (Fasilitasi Pembelajaran Kimia Siswa dan Penyuluhan Pertanian) - Cucun Alep Riyanto; Sarawinda Hutagalung; November Rianto Aminu; Jumiyati Jumiyati; Pandu Krisnawan; Nur Ayu Hidayati; Ratu Anggriani Tangke Parung; Samuel Yoga Saputra; Elizabeth Elizabeth; Maria Githania Maya Krisnawati; Yos Saputra Halomoan (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2022)
Community service is undertaken effectively to implement knowledge outside of lectures and train students' hard and soft skills as well. Community service was conducted in rural Jlarem, Gladagsari District, Boyolali Regency. The issues raised in this community service are related to the education of children and society’s agricultural knowledge. Therefore, this community service aims respectively to create programs that can improve learning methods for students and increase the people's insight in terms of managing agriculture and farm products in rural Jlarem. This community service is to address learning difficulties due to virtual learning activities during the COVID-19 pandemic and the scarcity of fertilizers and plant pests that are occurring in rural Jlarem. The method used in education was regularly tutoring with materials that have been prepared and followed by fun experiment s. Meanwhile, the agriculture tutorial was conducted by combining the presentation of the material by speakers and the following discussion. The satisfaction value is conducted by assessing questionnaires that are distributed to participants. The result of this community service is the implementation of learning guidance, and an agricultural extension program acquired a 3.6 GPA predicate of user activity respectively succeed.